Save the cat! Writes a young adult novel : the ultimate guide to writing a YA Bestseller - Brody, Jessica, ....- (California : Ten Speed Press, 2023)
In Save the Cat! Writes a Young Adult Novel, prolific author and story coach Jessica Brody presents a comprehensive story structure guide for anyone who wants to write a young adult novel by applying the famed Save the Cat! screenwriting methodology to the world of YA fiction. In this book, you will learn: - The fifteen "beats" (or plot points) that are necessary for crafting a successful story with a compelling character arc--including the Opening Image, Catalyst, Fun and Games, Bad Guys Close In, Dark Night of the Soul, and Finale - The ten universal story genres that will help you drill into what makes your type of story work, including those most commonly found in young adult novels like Rites of Passage, Superhero, Buddy Love, Institutionalized, and Golden Fleece - Quirky, original insights and writing tips like "Save the Cat," the "Shard of Glass," and the "Dark Night Epiphany," that help you craft a story that will thrill and captivate teen readers Filled with practical advice, easy-to-follow templates, and "beat sheets" analyzing the structure of popular young adult novels such as Leigh Bardugo's Six of Crows, John Green's The Fault in Our Stars, and Lois Lowry's The Giver, this book is the ultimate reference for anyone who's ever dreamed of writing their own young adult bestseller.
Keywords: Storytelling